The self-care situation analysis of reproductive-aged women in Tehran: a survey study - Masoumeh Simbar; Zahra Kiani; Zeinab Nasiri; Nahid KhodaKarami; Soheila Nazarpour; Farzaneh Rashidi Fakari; Sepideh Keyvanfar; Hamid Alavi Majd (BMC, 2023)
Abstract Background Along with a global increase in the prevalence of infectious and non-communicable diseases, self-care with an emphasis on reproductive health Self-care has received special attention. Given the importance of women's health, assessment of their self-care status using a valid and reliable tool seems to be necessary to determine the needs for future women's reproductive health promotion interventions. The present study aimed to assess the women's self-care at reproductive age in Tehran, to determine women's health needs based on global guidelines for women's health. Methods This was a descriptive cross-sectional study on 1051 women of reproductive age, living in Tehran. The Subjects were recruited using a multi-stage sampling method. The women completed a socio-demographic and valid and reliable questionnaire to assess their self-care status. The data were analyzed using SPSS 24 and by Pearson, Spearman, ANOVA, and regression tests. Results The mean score of self-care was 49.57 ± 23.50% in the reproductive-aged women. The lowest scores were related to psychosocial health (32.12 ± 29.93%) and reproductive-sexual health (49.74 ± 27.99%) respectively. There were significant positive correlations between the self-care and women's education level (r = 0.180; p < 0.01), and husband's education level (r = 0.272; p < 0.01), while there was a negative significant correlation between the self-care and the family size (r = - 0.135; p < 0.01). Conclusion The findings showed inadequate self-care among reproductive-aged women in Tehran. The most important challenge in their self-care behaviors was related to psychosocial and reproductive-sexual health. It seems to provide a package for promoting women's self-care in four areas of physical, psychosocial, reproductive-sexual health, and screening tests, with an emphasis on the first two priorities, namely psychosocial and reproductive health necessary in Tehran.